Efeitos De bioestimulante na emergência de plântulas de maracujazeiro ‘Roxinho Do Kênia’ - Ferraz, Rafael Augusto [UNESP]; Souza, Jackson Mirellys Azevêdo [UNESP]; Santos, Adelana Maria Freitas [UNESP]; Gonçalves, Bruno Henrique Leite [UNESP]; Dos Reis, Luis Lessi; Leonel, Sarita [UNESP] (My University, 2014)
The increase in market demand for fresh fruits along with the high price of passion fruit juice in domestic and international markets has increased the interest in fruit, especially the purple passion fruit in the center south of the country seeking to export. This study aimed to evaluate the effects of plant growth regulator on the emergence and development of seedlings of passion ‘Roxinho of Kenya’ when propagated sexually. The treatments consisted of concentrations of commercial product Stimulate®: control (no biostimulant); 6; 12; 18; 24 and 30 mL.kg-1of seed. It were evaluated the percentage of seedling emergence, number of leaves, aerial part dry weight, stem and root (g), root length (mm), diameter and stem length (mm), leaf area and chlorophyll ‘a’ and ‘b’. The application of bio-stimulant in doses of 6 and 12 mL.kg-1promotes increased percentage of seedling emergence of Passiflora edulis Sims in a shorter time. The use of it also promotes the development of seedlings, with better results for the dose of 12 and 24 mL.kg-1treated seeds.
Effects of emergency in biostimulant seedling of passion fruit ‘roxinho of kenya
Keywords: Development. Stimuate®; Passiflora edulis Sims; Plant regulator; Seedling production; Stimuate®